Encystment Induces Down-Regulation of an Acetyltransferase-Like Gene in Acanthamoeba castellanii - Steven Rolland; Luce Mengue; Cyril Noël; Stéphanie Crapart; Anne Mercier; Willy Aucher; Yann Héchard; Ascel Samba-Louaka (Pathogens, 2020)
Acanthamoeba castellanii is a ubiquitous free-living amoeba. Pathogenic strains are causative agents of Acanthamoeba keratitis and granulomatous amoebic encephalitis. In response to adverse conditions, A. castellanii differentiate into cysts, which are metabolically inactive and resistant cells. This process, also named encystment, involves biochemical and genetic modifications that remain largely unknown. This study characterizes the role of the ACA1_384820 Acanthamoeba gene during encystment. This gene encodes a putative N-acetyltransferase, belonging to the Gcn5-related N-acetyltransferase (GNAT) family. We showed that expression of the ACA1_384820 gene was down-regulated as early as two hours after induction of encystment in A. castellanii. Interestingly, overexpression of the ACA1_384820 gene affects formation of cysts. Unexpectedly, the search of homologs of ACA1_384820 in the Eukaryota gene datasets failed, except for some species in the Acanthamoeba genus. Bioinformatics analysis suggested a possible lateral acquisition of this gene from prokaryotic cells. This study enabled us to describe a new Acanthamoeba gene that is down-regulated during encystment.